2002
DOI: 10.1002/ejsp.126
|View full text |Cite
|
Sign up to set email alerts
|

The bystander effect and social control behavior: the effect of the presence of others on people's reactions to norm violations

Abstract: Observers of deviant social behavior sometimes communicate disapproval directly or indirectly to the perpetrator of a deviant act. This reaction has been termed 'social control'. Three field studies were conducted to explore the influence of the number of bystander-observers on the likelihood of social control. We predicted that the presence of others would inhibit people's tendency to communicate their disapproval to the deviant but only if personal implication was low. In the first study, we measured partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
139
0
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(160 citation statements)
references
References 35 publications
(16 reference statements)
12
139
0
9
Order By: Relevance
“…First, the predicted behavior assessed in our study is completely consistent with the findings of Chekroun and Brauer (2002) who showed that approximatively 68% of their participants predicted that they would react toward an individual who litters in a neighborhood park. More importantly, Brauer, 2002) reported a very strong correlation between the self-reports and actual social control reaction in the same situations, including a littering situation (.84). We are thus comfortable with the assumption that self-reports of social control intentions are reasonable indicators of social control behavior.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…First, the predicted behavior assessed in our study is completely consistent with the findings of Chekroun and Brauer (2002) who showed that approximatively 68% of their participants predicted that they would react toward an individual who litters in a neighborhood park. More importantly, Brauer, 2002) reported a very strong correlation between the self-reports and actual social control reaction in the same situations, including a littering situation (.84). We are thus comfortable with the assumption that self-reports of social control intentions are reasonable indicators of social control behavior.…”
Section: Discussionsupporting
confidence: 89%
“…After reading the situation, participants were asked to indicate how they would react. They responded on a seven-point scale adapted from Chekroun and Brauer (2002): 0 ¼ no reaction, 1 ¼ indifferent, you look away, 2 ¼ loud audible sigh, 3 ¼ make a polite comment to the person about the incorrectness of her behavior, 4 ¼ ask the person if she would pick up her bottle, 5 ¼ command in authoritarian tone the person to pick up her bottle, and 6 ¼ make a personal insult in aggressive tone to the person. The two first responses are considered to be the expression of ignorance or absence of awareness of the deviant behavior and thus express the absence of intention to react toward the deviant behavior.…”
Section: Materials and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The bystander effect and a desire for anonymity by citizens may also contribute to the victimization of suitable targets in public spaces (Chekroun & Brauer, 2002). Fear of crime in these settings can influence the routine activities of people as well (Ceccato, 2016;Ceccato, 2014;Loukaitou-Sideris, 2014;Madan & Nalla, 2016;Wiebe, et al, 2014).…”
Section: Research On Transit Environments and Other Public Spacesmentioning
confidence: 99%
“…[12,82] Just visualizing a crowd makes you less likely to help/intervene. It is therefore difficult to explain the result here except as a response to experienced pressures to regulate social life at large scale.…”
Section: Discussionmentioning
confidence: 99%